Pursuing happiness - Christian Schubert (Max Planck Institute of Economics, 2012)
While research on subjective well-being abounds, comparatively little thought has been given to its practical policy implications. Two approaches to derive policy advice have emerged in the literature: One is organized in terms of the idea to maximize a hedonic social welfare function, the other focuses on the design of constitutional rules to facilitate the individuals' self-determined pursuit of happiness. We suggest to substantiate what it means to pursue happiness, in particular by drawing upon a psychologically informed account of preference learning. If extended in this direction, a notion of the pursuit of happiness has interesting practical policy implications.
Keywords: D03; D11; D60; 330; subjective well-being; happiness; welfare economics; preference learning; Lebensqualität; Zufriedenheit; Wirtschaftspolitik; Soziale Wohlfahrtsfunktion; Präferenztheorie; Lernprozess; Theorie